The consequences of a year of the COVID-19 pandemic for the mental health of young adult twins in England and Wales. Issue 4 (21st July 2022) - Rimfeld, Kaili; Malanchini, Margherita; Arathimos, Ryan; Gidziela, Agnieszka; Pain, Oliver; McMillan, Andrew; Ogden, Rachel; Webster, Louise; Packer, Amy E.; Shakeshaft, Nicholas G.; Schofield, Kerry L.; Pingault, Jean-Baptiste; et al.
Abstract : Background: The COVID-19 pandemic has affected all our lives, not only through the infection itself but also through the measures taken to control the spread of the virus (e.g. lockdown). Aims: Here, we investigated how the COVID-19 pandemic and unprecedented lockdown affected the mental health of young adults in England and Wales. Method: We compared the mental health symptoms of up to 4773 twins in their mid-20s in 2018 prior to the COVID-19 pandemic (T1) and during four-wave longitudinal data collection during the pandemic in April, July and October 2020, and in March 2021 (T2–T5) using phenotypic and genetic longitudinal designs. Results: The average changes in mental health were small to medium and mainly occurred from T1 to T2 (average Cohen d = 0.14). Despite the expectation of catastrophic effects of the pandemic on mental health, we did not observe trends in worsening mental health during the pandemic (T3–T5). Young people with pre-existing mental health problems were disproportionately affected at the beginning of the pandemic, but their increased problems largely subsided as the pandemic persisted. Twin analyses indicated that the aetiology of individual differences in mental health symptoms did not change during the lockdown (average heritability 33%); the average genetic correlation between T1 and T2–T5 was 0.95, indicating that genetic effects before the pandemic were substantially correlated with genetic effects up to a year later. Conclusions: We conclude that on average the mental health of young adults in England and Wales has been remarkably resilient to the effects of the pandemic and associated lockdown.